Inter-individual variability in optimal current direction for transcranial magnetic stimulation of the motor cortex - Balslev, Daniela; Braet, Wouter; McAllister, Craig; Miall, R. Chris (Journal of neuroscience methods, 2007)
We evaluated inter-individual variability in optimal current direction for biphasic transcranial magnetic stimulation (TMS) of the motor cortex. Motor threshold for first dorsal interosseus was detected visually at eight coil orientations in 45° increments. Each participant (n=13) completed two experimental sessions. One participant with low test–retest correlation (Pearson's r<0.5) was excluded. In four subjects, visual detection of motor threshold was compared to EMG detection; motor thresholds were very similar and highly correlated (0.94–0.99). Similar with previous studies, stimulation in the majority of participants was most effective when the first current pulse flowed towards postero-lateral in the brain. However, in four participants, the optimal coil orientation deviated from this pattern. A principal component analysis using all eight orientations suggests that in our sample the optimal orientation of current direction was normally distributed around the postero-lateral orientation with a range of 63° (S.D.=13.70°). Whenever the intensity of stimulation at the target site is calculated as a percentage from the motor threshold, in order to minimize intensity and side-effects it may be worthwhile to check whether rotating the coil 45° from the traditional posterior–lateral orientation decreases motor threshold.